Intraoperative conformal optimization for transperineal prostate implantation using magnetic resonance spectroscopic imaging. - Zelefsky MJ; Cohen G; Zakian KL; Dyke J; Koutcher JA; Hricak H; Schwartz L; Zaider M (Cancer Journal)
PURPOSE: Recent studies have demonstrated that magnetic resonance spectroscopic imaging (MRSI) of the prostate may effectively distinguish between regions of cancer and normal prostatic epithelium. This diagnostic imaging tool takes advantage of the increased choline and creatine versus citrate ratio found in malignant, compared with normal, prostate tissue. The purpose of this report is to present our initial experience integrating MRSI data into an intraoperative computer-based optimization planning system for prostate cancer patients who underwent permanent interstitial I 125 implantation. The goal of this approach was to achieve dose escalation to intraprostatic tumor deposits on the basis of MRSI findings without exceeding the tolerance of adjacent normal tissue structures. MATERIALS AND METHODS: MRSI was obtained before surgery for four consecutive patients with clinically localized prostate cancer. The ratios of choline and citrate for the prostate were analyzed, and regions in which malignant cells were suspected to be present were identified. These ratios were calculated on a spatial grid overlying the axial MRSI of the prostate. MRSI coordinates containing these suspicious regions were registered to the intraoperative ultrasound images. A computer-based treatment planning system, which relied on a genetic algorithm, was used to determine the optimal seed distribution necessary to achieve maximal target volume coverage with the prescription dose and to maintain urethra and rectal doses within tolerance ranges. The treatment planning system was specifically designed to escalate the dose to MRS-positive voxels while at the same time achieving preferential sparing of surrounding normal tissues. Patients underwent transperineal interstitial implantation with I 125 by use of this intraoperatively generated plan. Postimplant computed tomographic scans were performed on the same day of the procedure in all cases, and dosimetric guidelines of the American Brachytherapy Society were used to assess implant quality. RESULTS: Based on the postimplant computed tomographic evaluation, the intraoperative optimization treatment planning program was able to achieve a minimum dose of 139% to 192% of the 144-Gy prescription dose to the MRS-positive voxels. The percentage of the prostate volume receiving 100% of the prescription dose ranged from 92% to 97%, and the dose delivered to 90% of the target for the target volume ranged from 96% to 124%. Despite the dose escalation achieved for the positive voxels, the urethral and rectal doses were maintained within tolerance ranges. The average and maximal rectal doses ranged from 28% to 43% and 69% to 115% of the prescription dose, respectively. The average and maximal urethral doses ranged from 66% to 144% and 118% to 166% of the prescription dose, respectively. CONCLUSIONS: Using this brachytherapy optimization system, we could demonstrate the feasibility of MRS-optimized dose distributions for I 125 permanent prostate implants. This approach may have an impact on the ability to select regions within the prostate to safely employ dose escalation for patients treated with permanent interstitial implantation and to improve outcome for patients with organ-confined prostatic cancers.